Inovasi Kaca Pintar: Pengaturan Pencahayaan Berbasis Sensor Panas Untuk Aplikasi Smart Home - Arif Hidayat; Tata Sutabri (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to develop a smart glass system with heat sensor-based lighting control for Smart Home applications. The developed system integrates temperature (thermal) sensors and light-dependent resistors (LDR) to detect temperature changes and light intensity in the room, allowing the automatic and energy-efficient adjustment of lighting. By using smart glass technology that can alter its transparency, the system is designed to create a comfortable environment for the occupants while reducing unnecessary energy consumption. The research includes system design, sensor selection and testing, hardware and software implementation, as well as system performance evaluation. The testing results show that the thermal sensor can accurately detect temperature changes, while the LDR can measure light intensity with precision. The system successfully adjusts the lighting based on temperature and light changes, saving up to 30% of the energy typically used for lighting. The system provides a more comfortable environment for the occupants, as the lighting is adjusted according to the surrounding conditions. However, there are challenges such as dependence on external conditions and relatively high implementation costs. This study recommends further development to improve the system's effectiveness and reduce production costs, enabling the wider application of this technology.